2016
DOI: 10.1085/jgp.201511452
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of fast skeletal myosin-binding protein C in zebrafish results in a severe skeletal myopathy

Abstract: MyBPC: A muscle protein for all seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 60 publications
0
25
1
Order By: Relevance
“…Structural and regulatory roles have been suggested for the MyBP-C family in both cardiac and skeletal muscles (4, 304, 322, 449, 604), although most of our knowledge stems from studies on cMyBP-C.…”
Section: Myosin Binding Protein-cmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural and regulatory roles have been suggested for the MyBP-C family in both cardiac and skeletal muscles (4, 304, 322, 449, 604), although most of our knowledge stems from studies on cMyBP-C.…”
Section: Myosin Binding Protein-cmentioning
confidence: 99%
“…Moreover, Abdul-Hussain and colleagues reported that sMyBP-C is the major MyBP-C isoform expressed during early myofibrillogenesis in cultured primary human skeletal myotubes, suggesting that it may be essential for sarcomeric assembly and maintenance (4). Recently, Li and colleagues indicated that knockdown of fMyBP-C in zebrafish larvae leads to development of a myopathic phenotype, characterized by shorter sarcomeres, wider interfilament spacing, and muscle weakness (322). Muscle function was also significantly impaired, and was characterized by reduced force production, prolonged time between stimulus and onset of contraction, and slower rates of contraction and relaxation (322).…”
Section: Myosin Binding Protein-cmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, while motion appeared normal under baseline conditions, these mutant fish exhibited a reduced “touch-escape” response, possibly suggesting that these mutations required some form of stress to show their true function. Knockdown of fsMyBP-C in zebrafish also resulted in skeletal myopathy, albeit without the severe body curvature described in ssMyBP-C knockouts [105]. These fsMyBP-C null fish exhibited sarcomeric disorganization, reduced active force production, and an increase in markers for muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Lattice spacing of contractile laments at 6 dpf was determined by small angle x-ray scattering (SAXS) using synchrotron radiation. as previously described [20,26,27] at beamline PO3 at Petra III, Deutsches Elektronen-Synchrotron (DESY) synchrotron facility in Hamburg Germany [28]. Larvae muscle preparations with aluminum clips were mounted between two hooks in a Kapton cuvette in the physiological solution as described (Sect.…”
Section: Small Angle X-ray Scatteringmentioning
confidence: 99%